2020
DOI: 10.1111/1751-7915.13595
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and nutrient function of intestinal bacterial communities in black soldier fly (Hermetia illucens L.) larvae in livestock manure conversion

Abstract: The potential utility of black soldier fly larvae (BSFL) to convert animal waste into harvested protein or lipid sources for feeding animal or producing biodiesel provides a new strategy for agricultural waste management. In this study, the taxonomic structure and potential metabolic and nutrient functions of the intestinal bacterial communities of BSFL were investigated in chicken and swine manure conversion systems. Proteobacteria, Firmicutes and Bacteroidetes were the dominant phyla in the BSFL gut in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 50 publications
(43 reference statements)
3
46
1
Order By: Relevance
“…We studied bacterial community dynamics to identify taxa that were more abundant during BSFL rearing and that were absent in the controls (i.e., substrates stored under the same environmental conditions but without larvae). As suggested by previous researchers (Zhao et al, 2017;Ao et al, 2020), we hypothesized that bacteria enriched in the rearing residue contribute to substrate decomposition. This could imply that pure-culture bacteria and/or defined bacterial mixtures comprised of these bacteria from the residue could potentially increase large-scale BSFL rearing.…”
Section: Common Fly Associated Bacteria Dominate the Rearing Residuementioning
confidence: 86%
See 2 more Smart Citations
“…We studied bacterial community dynamics to identify taxa that were more abundant during BSFL rearing and that were absent in the controls (i.e., substrates stored under the same environmental conditions but without larvae). As suggested by previous researchers (Zhao et al, 2017;Ao et al, 2020), we hypothesized that bacteria enriched in the rearing residue contribute to substrate decomposition. This could imply that pure-culture bacteria and/or defined bacterial mixtures comprised of these bacteria from the residue could potentially increase large-scale BSFL rearing.…”
Section: Common Fly Associated Bacteria Dominate the Rearing Residuementioning
confidence: 86%
“…Providencia spp., Dysgonomonas spp., Morganella spp., and Proteus spp. present in the BSFL residues, and absent in controls without larvae, are highly abundant in the BSFL guts (Ao et al, 2020;Cifuentes et al, 2020;Klammsteiner et al, 2020;Raimondi et al, 2020). Identification of Dysgonomonas, Providencia, Morganella, and Proteus in the posterior midgut of BSFL suggest that members of these genera may survive gut passage (Bruno et al, 2019).…”
Section: Common Fly Associated Bacteria Dominate the Rearing Residuementioning
confidence: 99%
See 1 more Smart Citation
“…Even though only a minor fraction of a community unveiled by sequencing methods is culturable ( Alain and Querellou, 2009 ; Prakash et al, 2013 ), the bacterial profile found within these culture-independent studies is to some extent comparable to that found via our approach. Overall, these studies reported that the most representative phyla are the Proteobacteria, the Firmicutes, the Bacteroidetes and to a lesser extent the Actinobacteria ( Jeon et al, 2011 ; Zheng et al, 2013 ; Wynants et al, 2018 ; Bruno et al, 2019b ; Jiang et al, 2019 ; Zhan et al, 2019 ; Ao et al, 2020 ; Klammsteiner et al, 2020 ; Liu et al, 2020 , 2021 ; Raimondi et al, 2020 ; Shelomi et al, 2020 ; Galassi et al, 2021 ; Wu et al, 2021 ). In our collection, these four phyla are also represented: the Proteobacteria (66.3%), the Firmicutes (30.2%), the Bacteroidetes (2.9%) and the Actinobacteria (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the gut microbial dynamics of these larvae are of specific interest to obtain insight in the insect’s physiology, and further, to increase the yield of the rearing or conversion process. In recent years, the literature available on the composition of the BSFL gut microbiota, possibly in relation with its substrate and other rearing factors, increased substantially, with examples of relevant studies including those of Jeon et al (2011) ; Zheng et al (2013) , Wynants et al (2018) ; Jiang et al (2019) , Ao et al (2020) ; Klammsteiner et al (2020) , Liu et al (2020) ; Raimondi et al (2020) and Shelomi et al (2020) . Based on the aforementioned studies, it can be concluded that a set of genera regularly occurs in the larval gut, such as Enterococcus , Providencia , Morganella , and Dysgonomonas , although relative abundances vary among and within studies.…”
Section: Introductionmentioning
confidence: 99%